Rethinking Cultural Narratives in Indonesian ELT: A Reflective Essay on Intercultural Competence in a Globalized Digital Society - Ade Septian Ridho (Universitas Negeri Surabaya, 2025)
This essay explores the need for a more inclusive cultural representation in English language teaching (ELT) materials in Indonesia, particularly for high school students. Drawing from personal experience and supported by relevant theories and studies, I question the dominant focus on English-speaking countries’ cultures in textbooks, despite the fact that most English communication today occurs among non-native speakers, especially within the ASEAN region. Using Byram’s (1997) Intercultural Communicative Competence (ICC) framework, I analyze how language and culture are deeply connected and argue for the inclusion of ASEAN cultures in ELT to better reflect learners' real communication needs. A textbook analysis based on research by Setyono and Widodo (2019) reveals a lack of ASEAN cultural content and limited opportunities for learners to critically engage with different cultural perspectives. The paper ends with practical recommendations for improving textbook content and teacher development, so learners can develop not just language skills but also the intercultural competence necessary for today's global and regional communication contexts.